EVALUASI SISTEM INFORMASI AKUNTANSI PENGENDALIAN KAS BERBASIS KOMPUTER PADA PERUSAHAAN INTERNET SERVICE PROVIDER (STUDI KASUS PENERAPAN APLIKASI MYOB V 13+ DI PT.LDP YOGYAKARTA) - Elly Astuti; Elva Nuraina (Assets: Jurnal Akuntansi dan Pendidikan, 2013)
The purpose of writing this paper is to evaluate the computer-based accounting system that has been used by PT. LDP for decision making by the parties concerned as well as provide additional references for further research. Data were obtained from interviews with the board of directors with miraculous and financial staff associated with the implementation of MYOB applications in PT. LDP Yogyakarta in 2011. The result shows that the use of MYOB accounting information systems has positive impact on the company's financial statement presentation primary for its timelines. However, the evaluation of the application system, there are some things that need to be repaired by PT. LDP so the accounting information that presented can be used for economic decision-making. Implications for further research is the design and development of internal control system for family owned businesses.